A Global Analysis of the Relationship between Concentrations of Microcystins in Water and Fish - Flores, Natalie M.; Miller, Todd R.; Stockwell, Jason D. (Frontiers in Marine Science, 2018)
Cyanobacteria, the primary bloom-forming organisms in fresh water, elicit a spectrum of problems in lentic systems. The most immediate concern for people and animals are cyanobacterial toxins, which have been detected at variable concentrations in water and fish around the world. Cyanotoxins can transfer through food webs, potentially increasing the risk of exposure to people who eat fish from affected waters, yet little is known about how cyanotoxins fluctuate in wild fish tissues. We collated existing studies on cyanotoxins in fish and fresh water from lakes around the world into a global dataset to test the hypothesis that cyanotoxin concentrations in fish increase with water toxin concentrations. We limited our quantitative analysis to microcystins because data on other cyanotoxins in fish were sparse, but we provided a qualitative summary of other cyanotoxins reported in wild, freshwater fish tissues. We found a positive relationship between intracellular microcystin in water samples and microcystin in fish tissues that had been analyzed by assay methods (enzyme-linked immunosorbent assay and protein phosphatase inhibition assay). We expected microcystin to be found in increasingly higher concentrations from carnivorous to omnivorous to planktivorous fishes. We found, however, that omnivores generally had the highest tissue microcystin concentrations. Additionally, we found contrasting results for the level of microcystin in different tissue types depending on the toxin analysis method. Because microcystin and other cyanotoxins have the potential to impact public health, our results underline the current need for comprehensive and uniform detection methods for the analysis of cyanotoxins in complex matrices.